Severe 25(OH)vitamin-D deficiency: A risk factor for development of gestational diabetes mellitus. Issue 2 (March 2019) - Rajput, Rajesh; Vohra, Shaweta; Nanda, Smiti; Rajput, Meena
Abstract: Objective: To estimate the level of 25 (OH)vitamin D in gestational diabetes mellitus (GDM) and to find the correlation between level of 25(OH)vitamin D and GDM. Materials and methods: The study was conducted on 50 diagnosed patients of GDM attending antenatal clinic in the obstetrics and gynecology department of Pt. B.D. Sharma PGIMS, Rohtak. 50 age and gestational age matched normoglycemic women were taken as control group. Procedure of study was explained to the participants and informed consent was taken. Results: GDM women had higher age, BMI, and positive family history of type 2 DM as compared to pregnant women without GDM. The mean vitamin D in GDM women was 32.64 ± 24.33 nmol/L while in controls it was 39.90 ± 21.86 nmol/L(P = 0.033). The prevalence of severe vitamin D deficiency(<25 nmol/L) was found to be 44% among GDM women (22 out of 50 GDM women) and 20% among women with normoglycemia (10 out of 50 normoglycemic controls) with significant p value of 0.010 and odds ratio of 1.833. GDM women with BMI>25 kg/m 2 had 1.799 times chances to be severely deficit in vitamin D than women with BMI<25 kg/m 2 6 GDM women had mild vitamin D deficiency (>50 but <75 nmol/L) and 16 had moderate deficiency (>25 but <50 nmol/L). Only 6 GDM patients were found to be sufficient for vitamin D(>75 nmol/L). Conclusion: Severe vitamin D deficiency in second trimester of pregnancy is significantly associated with elevated risk for GDM.